The ecological impacts of pollution on a river ecosystem: a community index and stable isotope approach - Gininda, Simphiwe Linah (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
For decades, urbanized rivers have been modified to meet the needs of constantly expanding human populations in many countries around the world. The Bloukrans River in Grahamstown is one of the polluted and structurally modified urban rivers in South Africa, and there is no published information regarding its water quality and ecological status. Water quality is threatened by human activities including the disposal of treated and raw sewage, livestock farming, and agriculture. This study was conducted to determine the ecological status of the river by assessing its biological, chemical, and physical components in relation to man-mediated activities. Biological responses of macroinvertebrates were used to assess changes in water quality through space and time based on the South African Scoring System version 5 and the Average Score per Taxon water quality indices. The results showed poor water quality due to high nitrate and ammonium concentrations derived from sewage, and channel modifications by agricultural activities and dumping of solid waste. Channel width, water depth, dissolved oxygen, nitrate, and ammonium concentrations were the main drivers of macroinvertebrate distribution patterns and had the most influence on the variability in macroinvertebrates taxa richness, diversity and abundance. Diatoms were also used to assess water quality, specifically to indicate the trophic status of the river based on changes in the Trophic Diatom Index. The results suggested that the Bloukrans River was eutrophic during the course of this study. However, the trophic status varied with freshwater input, resulting in mesotrophic conditions during flooding and eutrophication in dry seasons. Changes in pH, phosphate concentration, water velocity (current speed), and temperature influenced the distribution of diatoms in the Bloukrans River. However, only pH was important at the community level and significantly influenced diatom abundances. Stable nitrogen isotope ratios (S15N) of autotrophs and primary and secondary consumers revealed noticeable differences between tissues of organisms exposed to treated sewage and those without any exposure. The S15N values in biota occurring above the sewage treatment discharge point were low, and those collected below the sewage point were higher. Although fertilizer derived nitrogen is generally depleted in 15N, agriculture-derived nitrogen could not be excluded as a possible source since animals at the sample site that was most affected by agricultural activities had the highest S15N values. This study provided valuable information on the ecological status of the Bloukrans River and identified the major activities associated with reduced biodiversity and water quality.
Keywords: Water -- Pollution -- Bloukrans River; Water quality -- South Africa -- Makhanda; Stream ecology -- South Africa -- Makhanda; South African Scoring System; Sewage disposal in rivers, lakes, etc. -- South Africa -- Makhanda; Agricultural ecology -- South Africa -- Makhanda; Agricultural pollution -- South Africa -- Makhanda